2020
DOI: 10.1080/02673843.2020.1775099
|View full text |Cite
|
Sign up to set email alerts
|

Integration of immigrant youth in Sweden: does sport participation really have an impact?

Abstract: Sport participation for youth with immigrant background is often argued to play an important role for migrant youth integration into their new host society. Although few well sampled longitudinal studies has been conducted. The aim of this study was to study the impact that sport participation has on two integration-related outcomes (problem behaviours and native friends) by using the Swedish version of the longitudinal CILS4EU study. The multi-group latent growth curve models showed that although youth active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 53 publications
(75 reference statements)
1
12
0
Order By: Relevance
“…For example, Neville et al (2021) found that organized sport was associated with a decrease in troubled behavior among boys, but no significant decreases were found for girls; neither was any prosocial effect due to sport present. Likewise, Lundkvist et al (2020) detected an effect on sport’s capacity to promote friendship, but only to a (very) small degree. Growing as a field of its own, sport for development (SFD) has emerged as a response to the increasing use of SFD outcomes.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, Neville et al (2021) found that organized sport was associated with a decrease in troubled behavior among boys, but no significant decreases were found for girls; neither was any prosocial effect due to sport present. Likewise, Lundkvist et al (2020) detected an effect on sport’s capacity to promote friendship, but only to a (very) small degree. Growing as a field of its own, sport for development (SFD) has emerged as a response to the increasing use of SFD outcomes.…”
Section: Introductionmentioning
confidence: 97%
“…Sport is thus not a socialization vehicle per se but provides a context in which socialization may occur. Yet, it is also evident that bridging rarely occurs ( Walseth, 2016 ; Lundkvist et al, 2020 ), which also points to the need to re-organize how we think about sport as an arena for (inter-ethnic) friendship.…”
Section: Introductionmentioning
confidence: 99%
“…As O'Driscoll et.al (2014) emphasize, a high level of integration has a positive nexus to participation in sports, and as Penninx and Garcés-Mascareñas (2016) point out, integration as a two-way process is more likely to occur in intercultural meetings in everyday activities. However, participation does not automatically lead to integration (Walseth, 2004;Spaaij, 2012;Lundkvist et al, 2020). Interethnic bridges between teammates are often limited to the sports field (Walseth, 2004;Spaaij, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…These come with advantages such as getting to know friends who can provide emotional and psychological support, provide a familial-like environment, help them learn the Swedish language and culture, and facilitate access to services and job opportunities easily. Sports and physical exercises create new beginnings for international people to explore and enjoy previously exciting activities and hobbies (Lundkvist et al, 2020;Malm, Jakobsson & Isaksson, 2019), similar to a feeling before the pandemic outbreak. International students have been able to socialise and have outdoor parties in regulated numbers, but they are still cautious about the standard operating procedures for COVID-19.…”
Section: "I'm a Sports Person I Play Football Now With A Club And I H...mentioning
confidence: 99%